Alat kendali sistem kelistrikan rumah berbasis Raspberry - Yunus Tjandi; Muhammad Yahya; Syarifuddin Kasim (Seminar Nasional LP2M UNM, 2019)
This study aims to: (1) produce a software prototype of a Raspberry-based electrical system control device to control electrical devices (electric safety / MCB, electric lights, TV, heating, and KKB), a house / building using a smartphone, (2) produce Control Tool Raspberry-based electrical system that functions to control electrical devices, use software that has been made, (3) build interfaces and applications Raspberry-based control devices, using smartphones to control electrical devices of a house / building, both at close range and from a distance far away, so it is safe from danger Short circuit. Data collection in this study uses interview techniques with control experts, literature techniques, and direct measurement techniques for the control devices used. The data analysis method used in this research is logic-based on the Raspberry-based control system using a Smartphone. The results showed that: 1) Control Tool Software Raspberry-based electrical system is functioning properly, this is evidenced by the functioning of all control systems, both on the security system (MCB), and for various controlled loads, 2) Electricity-based Control Systems Raspberries made to control equipment, have functioned well, this has been proven in the research trials using Smartphones, 3) Application and Interface of Raspberry-based Control Systems that have been made to function properly, this is evidenced by the results of the control system trial , using a Smartphone.